Computer training and professional library activities in Nigeria (2006)
This paper investigated computer training and professional library activities in Nigeria. Stratified quota sampliing technique coupled with questionnaire method was used for data collection. There were 260 subject from the libraries in the south-west Nigeria out of which 245 responded and 213 copies of their questionnaire were used for analysis. The reliability coefficient of the questionnaire used for data collection was α=0.82 using test-retest method. The study found that there was no significant correlation between the length of computer training and improved professional library activities of subjects(r=0.14,P>0.05); there was no significant difference between the ages (years) of the subjects with respect to thier improved professional library activities (F=0.044,P> 0.05); there was no significant difference between the computer training recieved on improved professional library activities of the subjects based on thier place of work. (F=2.209, P>0.05); but there was a significant relationship between the educational qualifications, computer training and improved professional library activities of subject R=0.28507, P< 0.05). Suggestions were offered on how to make computer training improve professional activities of the library personnel.